Aerial photography, LiDAR volumetric change and LiDAR cross-shore profile protocols and shoreline error at Scolt Head Island, North Norfolk Coast, UK - James Alastair Pollard; Susan M Brooks; Thomas Spencer (PANGAEA, 2018)
This paper presents a novel reference dataset for North Norfolk, UK, that demonstrates the value of harmonising coastal field-based topographic and remotely sensed datasets at local scales. It is hoped that this reference dataset and the associated methodologies will facilitate the use of topographic and remotely sensed coastal datasets, as demonstrated here using open-access UK Environment Agency datasets. Two core methodologies, used to generate the novel reference dataset, are presented. Firstly, we establish a robust approach to extracting shorelines from vertical aerial photography, validated against LiDAR (Light Detection and Ranging) and coastal topography surveys. Secondly, we present a standard methodology for quantifying sediment volume change from spatially continuous LiDAR elevation datasets. As coastal systems are monitored at greater spatial resolution and temporal frequency there is an unprecedented opportunity to determine how and why coastal systems have changed in the past with a view to informing future forecasting. With revelation of trends that suggest increasing coastal risk, coastal change research is needed to inform the management and protection of coasts.
Supplement to: Pollard, James Alastair; Brooks, Susan M; Spencer, Tom (2019): Harmonising topographic & remotely sensed datasets, a reference dataset for shoreline and beach change analysis. Scientific Data, 6(1), 42, https://doi.org/10.1038/s41597-019-0044-3